Implementasi Prinsip Animasi dalam Gerak Personifikasi Tokoh di Film Animasi Lakontara - Putra, Raden Raihan Pradipta Andrika; Panindias, Asmoro Nurhadi (ISI Press Institut Seni Indonesia Surakarta, 2023)
GEMASTIK is a competition among college students from all over Indonesia that is based on the utilization of Information and Communication Technology. Animation is one of the competition categories in GEMASTIK. Lakontara Animation participated in this competition by showcasing the story of Ketoprak art through personified characters to convey information. The values and impressions portrayed in each scene will create communication with the audience. The personified characters in this animation are objects that have to be visually presented as humans, even though they are not physically human. This is achieved by implementing animation principles in the movements of the characters in each scene. The movements of their bodies and facial expressions will represent the characters' nature and personality. The implementation of these principles has been successfully carried out in the Lakontara Animation, resulting in a significant impact on the movements of the personified characters, such as the gamelan, stage properties, and tablets as messengers to the audience, making the scenes come to life and conveying the values and impressions effectively